The Economic Roots of the Rise of Trumpism - John Komlos (Center for Economic Studies and ifo Institute (CESifo), 2018)
Donald Trump won the election in 2016 largely because enough voters in three states, all in the Rustbelt, who had voted for Barack Obama in both 2008 and 2012, switched their vote from Democratic to Republican. Economic dislocations played a crucial role in these swing states or democratic strongholds to persuade many voters to take the dramatic step to vote for an anti-establishment candidate even if that meant a leap of faith into the unknown. The sources of the dislocation were the development of a dual economy characterized at one end by low and stagnating wages, increasing debt, downward social mobility, declining relative incomes, and the hopelessness accompanying them while at the other end of the income distribution the economy was simply booming. This was longer than a three-decade process that started with Reaganomics and its tax cuts that privileged the rich and conferred immense wealth, and its concomitant, political power, on them. Reaganomics also accelerated the decline in the power of unions which had supported the middle class. The process continued under Bill Clinton's administration and its continuing both financial deregulation and of hyper-globalization. George Bush continued to pamper the superrich with his tax policies. The process culminated with Barack Obama's bailing out the superrich and his benign neglect of Mainstreet. Five administration's disinterest in the social group Hillary Clinton referred to flippantly as “the deplorables” culminated in the revolt of the masses in favor of an incompetent strongman by overthrowing the establishment captured by such chants at Trump rallies as “Lock her up!”, “USA!”, “Build the wall”, or “Drain the swamp” (i.e., in Washington D.C.).
Keywords: A10; 330; political economy of populism